Is climate change really a threat to business? Exploratory evidence from the wine industry - Galbreath, Jeremy (ANZAM, 2011)
This study explores the climate change issue with a sample of wine firms in Australia. Using a qualitative, inductive approach, the results challenge the extent to which climate change is a salient stakeholder, while demonstrating that the phenomenon may, in fact, be beneficial. The study further finds that firms engage in actions that both mitigate and adapt, although response is not always specifically directed towards climate change. Implications of the findings are discussed and propositions put forth.